Kewenangan Keuchik di Gampong Tumpok Teungoh Kota Lhokseumawe - MASITAH, DWI PUTRI (Politeia: Jurnal Ilmu Politik, 2016)
Law on Governing Aceh (UU No. 11/2006) states that Gampong or by any other name is the un-ity of the legal community who are under Mukim and led by keuchik or by any other name has the right to administer its own internal affairs. This study is the study of the authority of keuchik in Gampong Tumpok Teungoh Banda Sakti sub-district of Lhokseumawe. The findings of this study are keuchik has seven kinds of authority. First, keuchik has the authority to lead the im-plementation of the Government Gampong; Second, fostering religious life and the implementa-tion of Islamic law as well as the preservation of customs and traditions in society; Third, foster the economy of the community; Fourth, maintain peace and order of society; Fifth, became jus-tice of the peace among the population in the village; Sixth, he proposed reusamGampong; se-venth, filed a Draft Budget Gampong; eighth, representing Gamponginside and outside the court and is entitled to appoint legal counsel to represent him. The method used is descriptive method.This research method isqualitative. Data collection techniques performed by the method of interviews.Keywords: Lecal community, authority, keuchik.